FLUJO DE FONDOS: PODEROSA HERRAMIENTA DE GESTIÓN EN LOS NEGOCIOS (PARTE II) - Porlles Loarte, José Angel (2005)
In the first part of this Funds Flow Series, was impacted in the conceptual framework of the different focus of construction of the Funds Movement State. In this second part al proceeds analysis of the impact and the connection of the diverse accounts of the General Balance and of the State of Results (EPG) in the Funds Movement State, for its correct interpretation and understanding of the changes, obtaining thus vital information that contributes to a better financial analysis of what happened with the origin and uses of funds, as well as its impact in the financial structure of the company. The reflexive and systematic management of this tool of analysis will harness the professionals linked in it takes of managerial decisions.